How anatomical impairments found on CT affect perfusion percentage assessed by SPECT/CT scan? - Seraphim, Daniel M.; Koga, Katia H. [UNESP]; Vacavant, Antoine; de Pina, Diana R. [UNESP] (Springer Nature, 2024)
Aim: CT images can identify structural and opacity alterations of the lungs while nuclear medicine’s lung perfusion studies show the homogeneity (or lack of) of blood perfusion on the organ. Therefore, the use of SPECT/CT in lung perfusion scintigraphies can help physicians to assess anatomical and functional alterations of the lungs and to differentiate between acute and chronic disease. Objective: To develop a computer-aided methodology to quantify the total global perfusion of the lungs via SPECT/CT images and to compare these results with parenchymal alterations obtained in CT images. Methods: 39 perfusion SPECT/CT images collected retrospectively from the Nuclear Medicine Facility of Botucatu Medical School’s Clinics Hospital in São Paulo, Brazil, were analyzed. Anatomical lung impairments (emphysema, collapsed and infiltrated tissue) and the functional percentage of the lungs (blood perfusion) were quantified from CT and SPECT images, with the aid of the free, open-source software 3D Slicer. The results obtained with 3D Slicer (3D-TGP) were also compared to the total global perfusion of each patient’s found on their medical report, obtained from visual inspection of planar images (2D-TGP). Results: This research developed a novel and practical methodology for obtaining lungs’ total global perfusion from SPECT/CT images in a semiautomatic manner. 3D-TGP versus 2D-TGP showed a bias of 7% with a variation up to 67% between the two methods. Perfusion percentage showed a weak positive correlation with infiltration (p = 0.0070 and ρ = 0.43) and collapsed parenchyma (p = 0.040 and ρ = 0.33). Conclusions: This research brings meaningful contributions to the scientific community because it used a free open-source software to quantify the lungs blood perfusion via SPECT/CT images and pointed that the relationship between parenchyma alterations and the organ’s perfusion capability might not be so direct, given compensatory mechanisms.
Keywords: 3D slicer; Lungs; Nuclear medicine; Quantification; SPECT/CT